High-resolution velocimetry in energetic tidal currents using a convergent-beam acoustic Doppler profiler. (16th July 2015) - Sellar, Brian; Harding, Samuel; Richmond, Marshall
Abstract: An array of single-beam acoustic Doppler profilers has been developed for the high resolution measurement of three-dimensional tidal flow velocities and subsequently tested in an energetic tidal site. This configuration has been developed to increase spatial resolution of velocity measurements in comparison to conventional acoustic Doppler profilers (ADPs) which characteristically use divergent acoustic beams emanating from a single instrument. This is achieved using geometrically convergent acoustic beams creating a sample volume at the focal point of 0.03 m 3 . Away from the focal point, the array is also able to simultaneously reconstruct three-dimensional velocity components in a profile throughout the water column, and is referred to herein as a convergent-beam acoustic Doppler profiler (C-ADP). Mid-depth profiling is achieved through integration of the sensor platform with the operational commercial-scale Alstom 1 MW DeepGen-IV Tidal Turbine deployed at the European Marine Energy Center, Orkney Isles, UK. This proof-of-concept paper outlines the C-ADP system configuration and comparison to measurements provided by co-installed reference instrumentation. Comparison of C-ADP to standard divergent ADP (D-ADP) velocity measurements reveals a mean difference of 8 mm s −1, standard deviation of 18 mm s −1, and an order of magnitude reduction in realisable length scale. C-ADP focal point measurements compared to a proximal single-beam reference show peak cross-correlation coefficient of 0.96 over 4.0 s averaging period and a 47% reduction in Doppler noise. The dual functionality of the C-ADP as a profiling instrument with a high resolution focal point make this configuration a unique and valuable advancement in underwater velocimetry enabling improved quantification of flow turbulence. Since waves are simultaneously measured via profiled velocities, pressure measurements and surface detection, it is expected that derivatives of this system will be a powerful tool in wave-current interaction studies.